Pengaruh Kepercayaan, Citra Merek Dan Persepsi Kemudahaan Terhadap Penggunaan E-Wallet (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2019) - Brily Suharto Risky; Nurhidayah Nurhidayah; Tri Sugiarti Ramadhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine and explain the effect of trust, Marek's image and perceived ease of use of e-wallets (a case study on FEB students at the Islamic University of Malang, class of 2019). This research is a quantitative type of research. The method used is multiple linear regression. The sampling technique uses the formula from Solvin with the calculation results of 86 samples. To solve the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously. Variable The Effect of Trust (X1), Marek's Image (X2) Perceived Convenience (X3) simultaneously significant use of E-Wallet (Y) And there is a partial influence between the Effect of Trust (X1), Marek's Image (X2) Perceived Convenience (X3) has a significant effect simultaneously Use of E-Wallet (Y)  Keywords: The Effect of Trust, Marek's Image, Perceived Convenience, Use of E-Wallet